Daiquiri: a web‐based user interface framework for beamline control and data acquisition. (29th October 2021) - Fisher, Stuart; Oscarsson, Marcus; De Nolf, Wout; Cotte, Marine; Meyer, Jens
Abstract : Daiquiri is a web‐based user interface framework for control system monitoring and data acquisition. Abstract : Daiquiri is a web‐based user interface (UI) framework for control system monitoring and data acquisition designed for synchrotron beamlines. It provides simple, intuitive and responsive interfaces to control and monitor hardware, launch acquisition sequences and manage associated metadata. Daiquiri concerns itself only with the UI layer; it does not provide a scan engine or controls system but can be easily integrated with existing systems.